A note on pairwise continuous mappings and bitopological spaces - Kilicman, Adem; Salleh, Zabidin (European Journal of Pure and Applied Mathematics, 2009)
We continue the study of bitopological separation axioms that was begun by Kelly and obtain some results. Furthermore, we introduce a concept of pairwise Lindelöf bitopological spaces, namely, p 2 -Lindelöf spaces, and their properties are established. We also show that p 2 -Lindelöf is not a hereditary property. Finally, we show that p 2 -Lindelöf is a p 2 -topological property.